CORRELATION BETWEEN ANXIETY LEVELS AND THE DISTANCE LEARNING APPROVAL DURING PANDEMIC ON BACHELOR OF NURSING STUDENTS AT THE AISYAH UNIVERSITY OF PRINGSEWU IN 2021 - Sandi, Meyl; Agustriyani, Feri; Kusuma, Anggi (Jurnal Keperawatan Respati Yogyakarta, 2021)
One of the lessons learned during the COVID-19 pandemic is the distance learning process. This process has an impact on students, namely experiencing anxiety. Severe anxiety experienced by students is caused by the occurrence of culture shock. Distance learning causes social isolation because there is no social and physical interaction. The research objective was to determine the correlation between anxiety levels and the distance learning process on bachelor of nursing students at the Aisyah University of Pringsewu in 2021. This type of research is a quantitative analytical survey with a cross-sectional approach. The sample in this research was 73 students. The implementation time has been carried out from April up to May 2021. The technique used simple random sampling. The research instrument used the HARS questionnaire with spearman rank test analysis. The results of data analysis show that there is a correlation between anxiety levels and the distance learning process at the Aisyah University of Pringsewu with the Spearman rank test, obtained p-value of 0.000 (<0.05), it is expected that respondents will always take something positive from the learning process during a pandemic like this. Improve the understanding of the material by looking for their references to support understanding of the material presented. Keywords: Distance Learning Approval; Anxiety; Covid-19